Development of convection in high temperature coil annealing furnaces using rotating cylinder technique. (25th January 2018) - Fatla, Oula M.H.; Valera-Medina, Agustin; Robinson, Fiona; Cichuta, Mark; Beynon, Nathan
Highlights: Rotating cylinders for generating fluid recirculation in batch annealing furnaces. Using CFD approach to test the validity of the proposed technique. The capability of the rotating cylinder on producing fluid recirculation. Rotating cylinders enhanced heat transfer and fluid mixing quality. Possibility of reducing hot-spots and energy usage during annealing process. Abstract: The present study investigates the usage of rotating cylinders to generate gas circulation inside high-temperature coil annealing furnaces during the annealing treatment of grain-oriented electrical steel. This technique has been investigated to reduce temperature differentials (hotspots) within the furnace space, a phenomenon that occurs due to extremely high temperatures, the static nature of the gas inside of the furnace and long operation conditions. Finite volume numerical simulation using ANSYS Fluent was performed to test the validity of the proposed technique. The numerical results showed fluctuations in velocity magnitude of the fluid in comparison with a case when the technique was not employed. This is because of the vortex generation under the effect of the cylinder rotation. The generation of turbulence enhances gas-mixing quality, and thus it would save a great amount of energy required for the process, producing a product with desired magnetic properties at lower cost.